A simple and green analytical method for determination of iron based on micro flow analysis - Senee Kruanetr (2018)
A simple, inexpensive and reagent-less colorimetric micro flow analysis (μFA) system was implemented in a polymethyl methacrylate (PMMA) micro fluidic manifold. A T-shaped micro channel on a PMMA chip was fabricated by laser ablation and topped with molded polydimethylsiloxane (PDMS). The fabricated μFA system was integrated with the optical components as detector and applied to the determination of iron in water samples. It is based on the measurement of Fe(III)-nitroso-R salt complex at 720 nm formed by the reaction between Fe(III) and nitroso-R salt in an acetate buffer solution pH 5. The proposed μFA consumed very small amount of reagent and sample, it released waste of less than 2.0 mL h-1. The relative standard deviation (R.S.D.) was less than 2% (n = 11) with the recovery of 98.7 ± 0.12 (n = 5). The linear range for the determination of iron in water samples was over the range of 0.05-4.0 μg mL-1with a correlation coefficient (r2) of 0.9994. The limit of detection (3σ) and limit of quantitation (10σ) were 0.021 μg mL-1and 0.081 μg mL-1, respectively with a sample throughput of 40 h-1. © 2007 Elsevier B.V. All rights reserved.